Economic effects of the coronavirus on the water sector (Academic Journal of Internal Affairs, 2020)
The containment of the virus needs co-ordinated actions of the member states and an international cooperation. For the water sector as a nationwide organisation subordinated the Ministry of Interior it is a new challenge, too and has to be settled together. In this situation the fighting needs a basic change of our rules of action. Although the organisation tries to minimize spreading out of the virus, but it must handle the tasks fixed in the valid statute regulations and other legal rules of the sector, too. The experiences already show that the calculable economic stability has already changed this year.
Keywords: COVID-19; water sector